Post-Maternity Privileges and Challenges Faced by Women in Private and Public Sector Banks in Haryana - Kaur, Mandeep; Verma, Dr. Ranjeet (The journal of contemporary issues in business and government, 2021)
The study on post-maternity privileges and challenges faced by women in private and public sector banks in Haryana could certainly be of special interest and significance to Haryana state’s banking sector since they would be concerned with the issues affecting the working womenfolk in the banking sector to streaming their objectives and strategies for the welfare and amelioration of working women after maternity. Hence the present study is a conscious attempt to ascertain empirically the extent of conflicting situations of post-maternity psychological challenges faced by working women encounter due to the changing and often incongruent role expectations in the context of family, child, profession, and societal norms. The present study is based on primary as well as secondary studies. The primary data have been collected from 370 working women respondents of public and private sector banks in Haryana. Random sampling method have been used for primary data collection. This area will be chosen because the study is mainly focusing on post-maternity privileges and challenges faced by women in private and public sector banks in Haryana. Area of research branch and respondents have selected through simple random sampling and banking sector will be categorized in two levels (private banks and public banks).